“Digital Translation in Urdu Literature: New Dimensions of Colonial Thought” - DR. SYED ZAHID HUSSAIN KAZMI (Zaban-o-Adab, 2025)
This critical paper presents a critical, intellectual exploration of the past, present and digital future of Urdu translation. The study highlights that although machine translation and digital systems have remarkably expanded the range, accessibility and interactivity of language, these very technologies have also revived colonial thought and consciousness in new forms. Beginning with the historical tradition of Urdu translation, the research draws upon the theoretical frameworks of Edward Said, Homi K. Bhabha, and Gayatri Spivak as foundational postcolonial perspectives. Within the context of the digital age, it offers a nuanced critical examination of issues such as algorithmic bias, Western centrality and the marginalization of Urdu. Ultimately, the study concludes that linguistic autonomy the development of indigenous data and principles of intercultural understanding are essential for preserving the intellectual and cultural identity of Urdu literature so that translation may transcend its colonial continuity and evolve into a creative, autonomous and intellectually independent practice.